2020
DOI: 10.1016/j.eurpolymj.2020.109839
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic carbene/Lewis acid-mediated ring-opening polymerization of propylene oxide. Part 2: Toward dihydroxytelechelic polyethers using triethylborane

Abstract: Propylene oxide (PO) is polymerized by metal-free ring-opening polymerization (ROP) at 25 °C using N-heterocyclic carbenes (NHCs) and triethylborane (Et 3 B) as a bicomponent catalytic system. Poly(propylene oxide)s with predictable molar mass up to 60 000 g.mol -1 and low dispersity (Ð < 1.10) were obtained without the occurrence of undesirable transfer reaction to the monomer. In presence of an alcohol as the initiator, the ROP of PO follows an anionic mechanism assisted by monomer activation improving the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…It is noted that these resonances disappeared for PGL after 24-hour of polymerization, indicating there was no epoxy group in the finally obtained polymers, implying that there should be some other initiation occurring, such as an intramolecular initiation resulting in cyclization or initiation through the moisture. 38 The disappearance of the epoxy group and other initiation approaches explain well that the obtained polymers show very low molecular weights (Table 1). Now, the main concern should be the ROP mechanism for epoxides other than GL.…”
Section: Papersupporting
confidence: 53%
“…It is noted that these resonances disappeared for PGL after 24-hour of polymerization, indicating there was no epoxy group in the finally obtained polymers, implying that there should be some other initiation occurring, such as an intramolecular initiation resulting in cyclization or initiation through the moisture. 38 The disappearance of the epoxy group and other initiation approaches explain well that the obtained polymers show very low molecular weights (Table 1). Now, the main concern should be the ROP mechanism for epoxides other than GL.…”
Section: Papersupporting
confidence: 53%
“…Also NHCs have been applied jointly with Et 3 B to prepare polyethers. 101 A closer inspection of polymerization kinetics revealed that a higher concentration of -OH functionalities ([hydroxyl], by adding a larger excess of alcohol initiator) entailed a significant slowdown of the polymerization rate. This is a crucial result, not only by having mechanistic implications, but also because epoxide polymerization in larger reactors is often started in the presence of a high amount of alcohol relative to epoxide (for safety reasons or to target oligomeric products).…”
Section: Epoxide Homopolymerizationmentioning
confidence: 99%
“…In order to broaden the applications of polyethers and avoid the presence of metal residues resulting from the use of metal complexes, several efforts have been made to prepare polyethers under metal-free conditions. Organocatalysts such as phosphazene bases, N -heterocyclic carbenes, N -heterocyclic olefins (NHO), ,, triethylborane (TEB) coupled with onium salts, and 9-borabicyclo[3.3.1]­nonane (9-BBN)-based bifunctional catalysts have been utilized for the ROP of epoxides. For instance, water was added as a transfer agent in the ROP of PO catalyzed by one of the 9-BBN bifunctional catalysts recently disclosed to obtain PPO telechelics .…”
Section: Introductionmentioning
confidence: 99%